Constituents of Cressa cretica L., A Halophytic Plant - Sunita, P.; Jha, S. (Asian Journal of Chemistry, 2012)
Three coumarins (1-3), four flavonoids (4-7) along with two phytosterols (8-9) were isolated from a halophytic plant Cressa cretica. Their structure established as coumarin (1), umbelliferone (2), daphnetin (3), quercetin (4), kaempferol (5), quercetin 3-O-b-D-glucoside (6), quercetin-3-O-a-L-rhamno-(1®6)-b-D-glucoside (7), stigmasterol (8) and b-sitosterol (9) on the basis of their comprehensive spectroscopic analysis including UV, IR, 1H NMR, 13C NMR, DART mass data.